2018
DOI: 10.1108/ajems-06-2017-0145
|View full text |Cite
|
Sign up to set email alerts
|

The impact of leverage on discretionary investment: African evidence

Abstract: Purpose The purpose of this paper is to explore the impact of leverage on firms’ discretionary investment in Africa. Design/methodology/approach The authors employ a dynamic panel data model estimated with generalised method of moments (GMM) estimation techniques on the panel data of listed African non-financial firms. A dynamic model and the generalised methods of moments estimations are handy in controlling for unobserved heterogeneity, endogeneity, autocorrelation, heteroscedasticity, etc. Findings In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
1
3
0
1
Order By: Relevance
“…Danso, Lartey, Fosu, Owusu-Agyei, and Uddin (2019), in research of sample of Indian firms during the 1995-2014 period, confirm the negative relationship of financial leverage with firm investment, which is stronger and significant for the firms with low growth opportunities, but no for firms with high growth opportunities. The same conclusion was reached for the African firms (Vengesai & Kwenda, 2018). K. Ahmad, Zulfiqar, Shah, Bilal, and Ahmad (2013), in the case of Pakistan for the 2000-2008 period, also find negative relationship between the firm leverage and investments, but the growth opportunities of the firm have no significance.…”
Section: Subsequent Researchsupporting
confidence: 58%
“…Danso, Lartey, Fosu, Owusu-Agyei, and Uddin (2019), in research of sample of Indian firms during the 1995-2014 period, confirm the negative relationship of financial leverage with firm investment, which is stronger and significant for the firms with low growth opportunities, but no for firms with high growth opportunities. The same conclusion was reached for the African firms (Vengesai & Kwenda, 2018). K. Ahmad, Zulfiqar, Shah, Bilal, and Ahmad (2013), in the case of Pakistan for the 2000-2008 period, also find negative relationship between the firm leverage and investments, but the growth opportunities of the firm have no significance.…”
Section: Subsequent Researchsupporting
confidence: 58%
“…Leverage signaling theory (Ross, 1977) mentions that debt is a credible sign reflecting the quality and the prospects of a company in the future, triggering positive reactions from the market upon the stock price of the company. A research carried out by Chowdhury and Chowdhury (2010), Bleck (2018), Oluwagbemiga (2013), Vengesai and Kwenda (2018) and Isaac (2014) confirmed that the capital structure has a positive and significant influence on the corporate market value. Trade-off theory (Modigliani and Miller, 1963), pecking order theory (Bhama et al, 2016), and leverage signaling theory (Ross, 1977) have been empirically proven.…”
Section: Introductionmentioning
confidence: 95%
“…Chen et al (2013) emphasized the role of corporate governance mechanisms and the lack of effective monitoring of managerial discretion may lead to the significant relationship between investments and cash flow. Vengesai and Kwenda (2018) investigated the impact of leverage on discretionary investment by using the panel data of non-financial firms in Africa. The results of their study revealed that leverage constraints investment with a disciplinary role avoiding over-investment.…”
Section: Literature Reviewmentioning
confidence: 99%